Community Partnership Empowerment Waste Utilization Pig Manure in P4S Sedana Sari Strait Village, Biansemal-Badung - Yuliartini, Made Sri; Wirajaya, Anak Agung Ngurah Mayun; Sukmadewi, Desak Ketus Tristiana; Setiawan, Tasya Amelia; Todo, Modesta Sriayuningsi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Community partnership empowerment was carried out at P4S Sedana Sari with the title